REPRESENTASI NILAI-NILAI SDGS MELALUI DINAMIKA KEPRIBADIAN TOKOH UTAMA DALAM KUMPULAN CERPEN KIOS PASAR SORE KARYA REDA GAUDIAMO - Riyan Prasetyo; Kenes Ratu Pawestri; Nugraheni Eko Wardani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
The increasing complexity of social and psychological issues in modern society calls for interdisciplinary approaches, including the use of literary works as a medium for reflecting on sustainable development values. This study aims to examine the representation of Sustainable Development Goals (SDGs) values through the personality dynamics of the main character in the short story collection Kios Pasar Sore by Reda Gaudiamo. This research employs a descriptive qualitative approach using the perspective of literary psychology, focusing on the interaction of id, ego, and superego in shaping the character’s behavior. The data consist of narrative excerpts and dialogues analyzed thematically to reveal the relationship between personality dynamics and SDGs values, such as social equality, empathy, justice, and well-being. The findings indicate that the main character experiences complex inner conflicts and psychological development, reflecting a balance between individual interests and social responsibilities. The representation of SDGs values emerges through the character’s responses to various personal and social life issues. These findings affirm that literary works can serve as a reflective medium for understanding global issues in a contextual manner. This study also contributes to strengthening literature studies based on global issues and enriching the perspective of applied linguistics in contextual literary text analysis.